The device of heat pipes and their design - Khusanov Hamid Gulyamovich; Yakubov Ulugbek Kutfidinovich (Genius Journals, 2023)
The main goal set for the new Uzbekistan is the development of alternative energy production, the active introduction of technology. In the country, alternative and renewable types of energy should account for at least half of the total energy consumption. Heat exchangers are designed to carry out heat exchange processes when it is necessary to heat or cool the process medium in order to process it or utilize heat
Keywords: energy production